SAT0200 Adherence to Therapy of Rituximab in Clinical Practice. NO Relation to Initial or Cumulative Dose Over the First 2 Treatment Years. (9th June 2015) - Einarsson, J.T.; Evert, M.; Kristensen, L.E.; Geborek, P.; Saxne, T.; Kapetanovic, M.C.
Abstract : Background: The optimal dosing for rituximab (RTX) in rheumatoid arthritis (RA) has been debated over the years, as the evidence from dose finding studies in RA are limited Objectives: To explore the impact of different initial doses of RTX (500 mgx2 vs 1000 mgx2 and cumulative RTX dose during the first 2 treatment years) on drug adherence and possible predictors of long-term adherence to treatment in rheumatoid arthritis (RA) patients in clinical practice. Methods: All RA patients starting RTX between January 2003 and April 2012 at the Departments of rheumatology in Malmö and Lund were prospectively included in the South Swedish Arthritis Treatment Register (SSATG). In addition, for validation of the RTX dose given and cause of treatment discontinuation, all medical records were subsequently scrutinized. We identified two different starting doses, 1000mg and 2000mg given in two divided doses. We calculated the cumulative dose at 12 and 24 months. Life-table estimation was used to determine drug adherence, adjusting for baseline characteristics. Logistic regression analysis was used to determine baseline predictors of adherence to treatment. Results: In total, 153 patients (74.5% female) with RA were included. 74 patients (48%) started treatment with 2000mg and 79 patients (52%) with 1000mg. Patients starting with 2000mg had significantly higher DAS28, HAQ and CRP at baseline. There were no differences in age, sex, disease duration, concomitant DMARDs or presence of autoantibodies at baseline between these groups. Median survival on drug was 44.4 months. A total of 75 (49%) patients withdrew from treatment during the first 5 years. No significant difference was seen for drug adherence when comparing starting doses. The cumulative doses of the drug within the first 2 years did not influence drug adherence. Predictor analysis identified methotrexate use and low disease activity at baseline as positively associated with drug adherence. The figure shows Kaplan-Meier curve for Rituximab drug adherence with different starting doses (no significant difference p=0.096) Conclusions: Neither different starting doses nor cumulative dose of rituximab during the first 2 treatment years influenced long-term adherence to therapy in RA patients treated in daily clinical practice. Methotrexate use and low disease activity at baseline was positively associated with drug adherence. Disclosure of Interest: None declared